The problem of the fetish - Pietz, William (The University of Chicago Press, 2022)
"The Problem of the Fetish gathers William Pietz's innovative writing on the fetish object and the history of the "fetish" as a concept. Engaging extensively with historical documents, Pietz traces the genealogy of fetishism from encounters between European colonizers and African communities in the sixteenth and seventeenth centuries to the emerging social sciences. Discussing the role of fetishism in anthropology, political economy, psychiatry, and law, he analyzes the relationship between the fetish and value, violence, sacrifice, and debt. To accompany Pietz's seven essays, this long-awaited volume includes a foreword by Francesco Pellizzi, editor of RES, the journal in which several of the essays originally appeared, and it also includes an introduction by Stefanos Geroulanos and Ben Kafka, who provide an invaluable guide to Pietz's thought. This book will speak to Pietz's multidisciplinary readership, continuing his legacy of engaging with questions of material culture, object agency, merchant capitalism, and spiritual power, and introducing the work of a powerful theorist to new generations of scholars and thinkers"--